780. How Much Does Prior Hospitalization Contribute to Readmission with Community-onset Clostridioides difficile Infection?. (31st December 2020) - Guh, Alice; Korhonen, Lauren C; Winston, Lisa Gail; Martin, Brittany; Johnston, Helen; Brousseau, Geoffrey; Basiliere, Elizabeth; Olson, Danyel M; Fridkin, Scott; Wilson, Lucy E; Perlmutter, Rebecca; Holzbauer, Stacy; et al.
Abstract: Background: Interventions to reduce community-onset (CO) Clostridioides difficile Infection (CDI) are not usually hospital-based due to the perception that they are often acquired outside the hospital. We determined the proportion of admitted CO CDI that might be associated with previous hospitalization. Methods: The CDC's Emerging Infections Program conducts population-based CDI surveillance in 10 US sites. We defined an incident case as a C. difficile-positive stool collected in 2017 from a person aged ≥ 1 year admitted to a hospital with no positive tests in the prior 8 weeks. Cases were defined as CO if stool was collected within 3 days of hospitalization. CO cases were classified into four categories: long-term care facility (LTCF)-onset if patient was admitted from an LTCF; long-term acute care hospital (LTACH)-onset if patient was admitted from an LTACH; CO-healthcare-facility associated (CO-HCFA) if patient was admitted from a private residence but had a prior healthcare-facility admission in the past 12 weeks; or community-associated (CA) if there was no admission to a healthcare facility in the prior 12 weeks. We excluded hospitals with < 10 cases among admitted catchment-area residents. Results: Of 4724 cases in 86 hospitals, 2984 (63.2%) were CO (median per hospital: 65.8%; interquartile range [IQR]: 58.3%-70.7%). Among the CO cases, 1424 (47.7%) were CA (median per hospital: 48.1%; IQR: 40.3%-57.7%), 1201 (40.3%) were CO-HCFA (median per hospital: 41.0%; IQR: 32.9%-47.8%), 350 (11.7%) were LTCF-onset (median per hospital: 10.0%; IQR: 0.6%-14.4%), and 9 (0.3%) were LTACH-onset. Of 1201 CO-HCFA cases, 1174 (97.8%) had a prior hospitalization; among these, 978 (83.3%) (median per hospital: 83.3%; IQR: 69.2%-90.6%), which consists of 32.8% of all hospitalized CO cases, had been discharged from the same hospital (Figure), and 84.4% of the 978 cases (median per hospital: 88.2%: IQR: 76.5%-100.0%) had received antibiotics sometime in the prior 12 weeks. Figure. Frequency of Cases Discharged in the 12 Weeks Prior to Readmission with Clostridioides difficile Infection (N=1138*) Conclusion: A third of hospitalized CO CDI had been recently discharged from the same hospital, and most had received antibiotics during or soon after the last admission. Hospital-based and post-discharge antibiotic stewardship interventions could help reduce subsequent CDI hospitalizations. Disclosures: Ghinwa Dumyati, MD, Roche Diagnostics (Consultant)